EFFECT OF COOPERATIVE MICRO-CREDIT SCHEME ON THE PERFORMANCE OF SMALL-SCALE BUSINESS IN OSUN STATE. (UNIZIK Journal of Marketing, 2026)
Cooperative microcredit schemes have become an important tool to serve micro and small enterprises (MSEs) in the developing economies especially in Nigeria where there is limited access to formal financing. This research enquires how cooperative microcredit programmes, namely the availability of cooperative credit, cooperative loans, savings mobilisation, and the non-financial support affect the performance of small owners of businesses in Osun State, Nigeria. The aim is to identify to what degree these elements contribute to the sustainability and growth of the enterprises as a whole and separately. The study took a quantitative survey research design wherein data was gathered from 224 small-scale business owners in the sampled cooperative societies. To evaluate the overall predictive power of cooperative microcredit schemes on performance of businesses, descriptive statistics, regression analysis and ANOVA were used. The model summary indicated a significant positive correlation between cooperative microcredit schemes and business performance (R =.925; R 2 =.856). The outcome of the ANOVA test proved the significant nature of the model in general F(4,308) = 450.771; p ≤ .000). Regression coefficients demonstrated that non-financial support contributed the most apparent contribution (β = 2.260, p ≤ .000) which was preceded by cooperative loans, savings mobilisation and access to credit. Business performance was significantly affected by all the predictors at the 5% level. The results confirm that cooperative microcredit programmes play a great role in improving the performance of small businesses in Osun State. The study recommended that cooperative micro-credit programmes should continue to be a viable tool toward enhancing the resilience in Osun State.
Keywords: Cooperative Microcredit, Performance, Savings Mobilisation, Entrepreneurship, Non Financial Support.